A comparative evaluation of gingival microleakage and internal voids in Class II composite restoration with two different lining techniques: An in vitro study - Rachana Shishodia; Virinder Goyal; Almas Shaikh; Aushili Mahule; Jay Dondani (Wolters Kluwer Medknow Publications, 2022)
Aim: The aim of this study was to evaluate the gingival microleakage and internal voids in Class II composite restoration restored with precure and co-cure lining techniques using stereomicroscopic method. Materials and Methods: Forty-five freshly extracted permanent multirooted human molar teeth were collected and used in the study. After surface debridement and scaling of all teeth, standard Class II mesio-occlusal cavities were prepared. Forty-five samples were randomly divided into three experimental groups (n = 15), and filled according to manufacturer's instructions. Group I was precure group, Group II was co-cure group, and Group III was only bulk fill. The finishing and polishing of the restorations was done after 24 h. Then, all the specimens were subjected to thermocycling for 500 cycles. The gingival microleakage and internal voids of all the groups were evaluated using dye penetration method. Samples were then sectioned and examined under the stereomicroscope at ×40. Readings obtained were subjected to statistical analysis using SPSS ver 20.0 (IBM Corp, ARMONK USA) and Chi-square test. Results: The statistical analysis revealed that extent of microleakage was maximum in Group II (co-cure), followed by Group III (only bulk fill) and Group I (precure). The gingival voids were maximum in Group III (only bulk fill), minimum in Group II (co-cure), and least in Group I (precure). The cervical voids were maximum in Group II (co-cure) and Group III (only bulk fill), followed by Group I (precure). The occlusal voids were maximum in Group II (co-cure) and similar in Group I (precure) and Group III (only bulk fill). Conclusion: The precure lining technique was better than co-cure lining technique in terms of both microleakage and internal voids.